Phenolic Acids in Selected Tropical Citrus (Asian Journal of Plant Biology, 2013)
In spite of wide research on plant phenolics, limited data are available on the phenolic acid content in selected tropical citrus. Phenolic acids are known to contribute health benefits to humans. In this study, free and ester conjugated phenolic acid in selected tropical citrus was successfully identified and quantified using Gas Chromatography Mass Spectrometry (GCMS). Citrus microcarpa, Citrus medica, Citrus hystrix and Citrus suhuiensis were among the tropical citrus analysed for their free and ester conjugated phenolic acids. C. microcarpa contains high amount of free and ester conjugated phenolic acid, which may suitable to be applied in health food products.
Keywords: Phenolics; GCMS; Citrus microcarpa; Citrus medica; Citrus hystrix; Citrus suhuiensis